THE NEXUS OF WATER, ENVIRONMENT AND WATER RESOURCE MANAGEMENT DILEMMA IN THE KANO: IN SEARCH OF A NEW GAME THEORY APPROACH - Abdulhamid, Adnan (FUDMA Journal of Sciences, 2023)
The demands for water is astronomically increasing due to population growth and diminishing opportunities to economically develop water supplies in Kano. In spite of the various plans to supply adequate potable water to the Kano Region, yet water is increasingly becoming difficult to get. The rapid increase in population coupled with uncertain climate may perhaps be the cause of the setbacks. The use of water, both surface and ground which is not easily renewable has adverse effect on the environment. The water crises in Kano is intensifying with no solution in sight. The critical options must actually resort to either due to scarce water resources, failure of governments to inadequate plan for safe water delivery system. Kano in terms of water resource crises is in like the prisoner’s dilemma as water, a common good for all, is no longer obtainable on sustainable basis. This paper attempt to look at the scenario as a dilemma for all nexus (environment, water, people and sustainability) of which a new approach needs to be encapsulated in solving the problem. Such approach is the Game theory